Crag is a GEF for Rab11 required for rhodopsin trafficking and maintenance of adult photoreceptor cells. - Bo Xiong; Vafa Bayat; Manish Jaiswal; Ke Zhang; Hector Sandoval; Wu-Lin Charng; Tongchao Li; Gabriela David; Lita Duraine; Yong-Qi Lin; G Gregory Neely; Shinya Yamamoto; et al. (PLoS Biology)
Rhodopsins (Rhs) are light sensors, and Rh1 is the major Rh in the Drosophila photoreceptor rhabdomere membrane. Upon photoactivation, a fraction of Rh1 is internalized and degraded, but it remains unclear how the rhabdomeric Rh1 pool is replenished and what molecular players are involved. Here, we show that Crag, a DENN protein, is a guanine nucleotide exchange factor for Rab11 that is required for the homeostasis of Rh1 upon light exposure. The absence of Crag causes a light-induced accumulation of cytoplasmic Rh1, and loss of Crag or Rab11 leads to a similar photoreceptor degeneration in adult flies. Furthermore, the defects associated with loss of Crag can be partially rescued with a constitutive active form of Rab11. We propose that upon light stimulation, Crag is required for trafficking of Rh from the trans-Golgi network to rhabdomere membranes via a Rab11-dependent vesicular transport.